2012
DOI: 10.1111/j.1600-0765.2012.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus cristatus ArcA interferes with Porphyromonas gingivalis pathogenicity in mice

Abstract: Xie H, Hong J, Sharma A, Wang B‐Y. Streptococcus cristatus ArcA interferes with Porphyromonas gingivalis pathogenicity in mice. J Periodont Res 2012; 47: 578–583. © 2012 John Wiley & Sons A/S Background and Objective:  Porphyromonas gingivalis has been implicated as one of the major pathogens in chronic periodontitis, an infectious disease affecting the majority of the adult population. We have previously demonstrated that a surface protein, arginine deiminase (ArcA), of Streptococcus cristatus represses produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…For instance, Streptococcus cristatus inhibits fimbrial gene expression in P. gingivalis through the signaling action of arginine deiminase [76]. Consistent with this finding, in human subgingival plaque, the distribution of the two organisms is negatively correlated [77]. Moreover, S. cristatus suppresses P. gingivalis –induced alveolar bone loss in a mouse model [77].…”
Section: The Complement Systemmentioning
confidence: 89%
“…For instance, Streptococcus cristatus inhibits fimbrial gene expression in P. gingivalis through the signaling action of arginine deiminase [76]. Consistent with this finding, in human subgingival plaque, the distribution of the two organisms is negatively correlated [77]. Moreover, S. cristatus suppresses P. gingivalis –induced alveolar bone loss in a mouse model [77].…”
Section: The Complement Systemmentioning
confidence: 89%
“…S. cristatus for example, induces downregulation of fimbrial gene expression in P. gingivalis through the signaling action of arginine deiminase [34]. Consequently, the distribution of P. gingivalis and S. cristatus in human subgingival plaque is negatively correlated, and S. cristatus attenuates P. gingivalis -induced bone loss in mice [35]. Such antagonistic interaction may lead to a ‘Red Queen’ effect, as P. gingivalis can induce cell death of another oral streptococcus, S. mitis [18].…”
Section: Interbacterial Interactionsmentioning
confidence: 99%
“…These unconventional B cells with autoreactive properties can provide a rapid T cell-independent antibody response to protect against infections [15]. Innate-like B cells in mice are composed of B1 cells [16], marginal zone (MZ) B cells [17] and other related B cells [18]. Recent studies indicated that innate-like B cells can link innate immunity to adaptive immune responses during infection [19, 20].…”
Section: Introductionmentioning
confidence: 99%